The development of PISA-like mathematics problem using Lombok Island contexts - Triutami, Tabita Wahyu; Novitasari, Dwi; Salsabila, Nilza Humaira (Mandalika Mathematics and Educations Journal, 2024)
The results of the PISA test for mathematical literacy in 2000–2018 and several previous studies show that students' critical thinking abilities in Indonesia are still relatively low. One of the reasons why students' critical thinking skills in Indonesia are low is because PISA-like problems have not been integrated evenly into mathematics learning. The aim of this research is to obtain a prototype of PISA-like mathematics problems in the context of Lombok Island that are oriented towards critical thinking skills that are valid, according to experts. This research is design research, which consists of 3 stages, namely analysis, design, and evaluation. The PISA-like problem that has been developed consists of twelve questions about space and shape, uncertainty, and data. Each set of questions consists of levels 1 to 6. Lombok Island contexts contained in the questions are Mount Rinjani, woven cloth with Subahnale and Alang motifs, the game of Dengkleng (Engklek), Gendang Beleq, and the Limbungan traditional house. At the evaluation stage, the validity of the development product is assessed by experts. The instrument used is a PISA-like problem validation sheet. The results of this research obtained a prototype of a PISA-like mathematics problem with a valid category, according to experts.